MnO2/PVP/MWCNT hybrid nano composites as electrode materials for high performance supercapacitor. (14th October 2016) - Jaggi, Neena; Sharma, Deepa; Sharma, Priya
Abstract: In this work, we developed supercapacitors with electrodes of manganese oxide (MnO2 ) and its nanocomposites with multiwalled carbon nanotubes (MWCNT) and polyvinylpyrrolidone (PVP) and studied the effect of the electrode material on various performance parameters of the supercapacitor. Cyclic voltammetry (CV) curves, galvanostatic charge/discharge measurement curves, XRD (x-ray diffraction), I-V characteristics and electrochemical impedance spectroscopy were employed for the characterization and analysis. CV curves were used to verify the supercapacitor behavior and the specific capacitance of the capacitors composed of the nanocomposite electrodes was calculated. I-V characteristics of MnO2 and MnO2/PVP/MWCNT were plotted and compared and conductivity measurements were also performed. Dielectric properties and equivalent series resistance were investigated using electrochemical impedance spectroscopy.